Modeling the reliability of the recycled water supply system in the conditions of global warming - Nazarenko, Oleksiy (Transfer of innovative technologies, 2018)
The issues of re-used water for recreational purposes were studied. The organic system of the enterprise may be a recycled system of water supply, hermetically sealed and equipped with automatic sensors, in every sense. It is also appropriate to use the remote controlling for thermal engineering parameters at factory sections using GPS modules. The importance of the corporate accent lies in the creation of social responsibility for service-managers and mechanics for each resource saving actions and future economic preferences. The most perspective and socially motivated direction of recycling is the modeling of balance of different water flows, considering the quality of chemical components. Currently, citizens and the administration of technoparks evaluate the clean water for such indicators: - water safety (sanitary and epidemiological requirements); - availability of water (quantity and quality); - stability water quality (water for ecosystems, water for health, water for sustainable development); - climate change and water security. To conform these indicators, an experiments were undertaken for different work modes of enterprise equipment. So to determine the optimal amount of fresh water supply, the second order of central orthogonal compositional planning is used. Mathematic model was obtained during scientific experiment. The system modeling considering hardness of water supply (1,5…10,5 m-q/l), the water alkalinity (1,5…10 m-q/l) gives the predictive data on the permissible coefficient of circulating water evaporation. On the basis of this simulation, it is advisable to recommend the preparation of artificial recharge supply with water hardness of 1,5 m-q/l at the enterprises. It will allow the system to operate at evaporation coefficient of 2,55 and save fresh water volume, equal to the production cycle. So the using of agricultural waste (chitosan) shows the possibility of its using for local sewage water cleaning of industrial cycles. The same solution can be used to feed vegetable and ornamental crops, in the local agricultural landscape of the enterprise. Development of the subsidiary production, allows to expand the range of production and to improve the company´s image.